Pengaruh Laju Pelepasan Fluor pada Resin Komposit Berfluor terhadap Kebocoran Tepi - Ariyani Faizah; Nilasary R. Suparno; Feby A. J. Pradana; Ericha Z. M. Diennya (e-GiGi, 2023)
Abstract: Composite resin is the most widely used restorative material due to its aesthetic properties, however, it has a drawback, namely edge leakage either by the polymerization process or by the release of components during the usage process. Therefore, composite resins containing fluorine has been developed as an effort to increase the success of restorative treatment by minimizing the occurrence of secondary caries or recurrent caries around the edges of the restoration. Composite resin releasing fluorine does not show a burst effect like the glass ionomer cement, but the pattern of fluorine release is low and constant. This was a pure laboratory experimental study. Samples were 25 maxillary 1st premolars prepared by class 1 cavity and filled with fluorine composite resin Tetric N-Ceram (Ivoclar Vivadent, Liechtenstein). Samples were divided into five groups that were immersed in sterile distilled water for 1, 7, 14, 21, 28 days, followed by 5% methylene blue for 4 hours. Edge leakage test using USB Digital Stereo Microscope used dye penetration method. Edge leakage was measured at the penetration depth of 5% methylene blue which was evaluated along the mesial and distal side of the restoration wall, then the side with the deepest color penetration was selected. The LSD test result showed that there was a significant difference between group A and the other four groups. In addition, there was no significant difference among the four groups (B, C, D and E). In conclusion, marginal leakage of the composite resin showed a constant value in each group according to a constant rate of fluorine release as well.    Keywords: fluorine release rate; fluorine composite resin; restoration; secondary caries       Abstrak: Resin komposit merupakan bahan restorasi yang memiliki kekurangan yaitu kebocoran tepi oleh proses polimerisasi maupun terlepasnya komponen. Resin komposit dengan kandungan fluor dikembangkan sebagai upaya untuk meningkatkan keberhasilan restoratif dengan meminimalkan terjadinya karies sekunder di tepi restorasi, dimana pelepasan fluornya tidak menunjukkan burst effect, melainkan pola pelepasan fluor rendah dan konstan. Penelitian ini bertujuan untuk mengetahui pengaruh laju pelepasan fluor pada resin komposit berfluor terhadap kebocoran tepi. Jenis penelitian ialah eksperimental murni laboratorik. Sampel berupa gigi premolar 1 rahang atas yang dipreparasi kavitas kelas 1 dan ditumpat menggunakan resin komposit berfluor sejumlah 25 buah. Sampel dibagi atas lima kelompok (A – E) untuk dilakukan perendaman dalam akuades steril selama 1, 7, 14, 21, dan 28 hari, dilanjutkan dengan methylene blue 5% selama 4 jam. Uji kebocoran tepi menggunakan USB Digital Mikroskop Stereo dengan metode penetrasi zat warna. Kebocoran tepi diukur pada kedalaman penetrasi methylene blue 5% dievaluasi sepanjang dinding restorasi sisi mesial dan distal, kemudian dipilih sisi dengan penetrasi warna terdalam. Hasil uji LSD menunjukkan terdapat perbedaan bermakna antara kelompok A dengan empat kelompok lainnya, dan tidak terdapat perbedaan bermakna antara keempat kelompok yaitu B, C, D dan E. Simpulan penelitian ialah kebocoran tepi resin komposit menunjukkan nilai konstan pada setiap kelompok sesuai dengan laju pelepasan fluor yang konstan juga. Kata kunci: laju pelepasan fluor; resin komposit berfluor; restorasi; karies sekunder